Antibacterial Activity of Salicornia brachiata, A Halophyte - G. Usha Rani, T. Manikandan, T. Neelakandan, (Journal of Phytology, 2009)
Antibacterial activity of Salicornia brachiata was studied by the agar diffusion and dilution methods. The methanolic extract of leaves of this species was more active than the aqueous extracts against Bacillus subtilis, Bacillus pumilus, Micrococcus luteus and Staphylococcus aureus.